Closure in Biblical Narrative. - Zeelander, Susan (BRILL, 2011)
Multiple and sometimes unexpected forms of closure in biblical narratives bring their stories to satisfactory close. Knowledge of these conventions and how they affect their stories is valuable to students of Bible and of narrative.